Targeting autophagy to treat neointimal hyperplasia in vascular disease - Yan, Runan; Tual-Chalot, Simon; Stellos, Konstantinos (Cardiovascular research, 2025)
This editorial refers to ‘Novel roles of Nrf3-Trim5 axis in vascular smooth muscle cell dysfunctions and neointimal hyperplasia’ by Q. Chen et al., https://doi.org/10.1093/cvr/cvaf084.Neointimal hyperplasia is a maladaptive response to vascular injury characterized by a pathologic thickening of the intimal layer of blood vessels. It is caused by multiple factors, including mechanical damage from interventional procedures, inflammatory responses within the vascular wall, haemodynamic changes, diabetes mellitus, and dyslipidemia.1 Neointimal hyperplasia appears in a variety of vascular diseases including atherosclerosis, post-stent restenosis, vascular graft disease, transplant vasculopathy, arteriovenous fistula disease, hypertensive vascular disease or vasculitis. In all these conditions, neointimal hyperplasia contributes to luminal narrowing, which impairs blood flow and can lead to ischaemic complications in the affected tissue or organ.1